2003
DOI: 10.1034/j.1600-079x.2003.00032.x
|View full text |Cite
|
Sign up to set email alerts
|

Five years survival in metastatic non‐small cell lung cancer patients treated with chemotherapy alone or chemotherapy and melatonin: a randomized trial

Abstract: Numerous experimental data have documented the oncostatic properties of melatonin. In addition to its potential direct antitumor activity, melatonin has proved to modulate the effects of cancer chemotherapy, by enhancing its therapeutic efficacy and reducing its toxicity. The increase in chemotherapeutic efficacy by melatonin may depend on two main mechanisms, namely prevention of chemotherapy-induced lymphocyte damage and its antioxidant effect, which has been proved to amplify cytotoxic actions of the chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
152
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(163 citation statements)
references
References 13 publications
6
152
0
5
Order By: Relevance
“…In addition, the average progression-free time was approximately 4 months for the group receiving chemotherapy alone and was 9 months for the melatonin group, and the majority of chemotherapyrelated toxicities had less than half the frequency in the melatonin and chemotherapy versus the chemotherapy alone group (Lissoni et al, 1999). Similar levels of increased chemotherapy tolerance, higher survival, and increased response were also found in a five-year study of 100 patients with non-small lung cancer (Lissoni et al, 2003). Other studies have reported consistent results of increased survival, tolerance, progressionfree time, as well as reductions in anxiety and pain (Vijayalaxmi et al, 2002).…”
Section: Melatonin Treatment and Anticancer Effectsmentioning
confidence: 55%
“…In addition, the average progression-free time was approximately 4 months for the group receiving chemotherapy alone and was 9 months for the melatonin group, and the majority of chemotherapyrelated toxicities had less than half the frequency in the melatonin and chemotherapy versus the chemotherapy alone group (Lissoni et al, 1999). Similar levels of increased chemotherapy tolerance, higher survival, and increased response were also found in a five-year study of 100 patients with non-small lung cancer (Lissoni et al, 2003). Other studies have reported consistent results of increased survival, tolerance, progressionfree time, as well as reductions in anxiety and pain (Vijayalaxmi et al, 2002).…”
Section: Melatonin Treatment and Anticancer Effectsmentioning
confidence: 55%
“…В группе с мелатонином было большее число объектив-ных ответов (11/34 по сравнению с 6/35), однако различия не были статистически значимы и увеличение медианы общей выживаемости с 19% до 44% (р<0.05) [46]. В по-следующем анализе данных было показано, что 6% боль-ных с НМРЛ, получавших химиотерапию с МЛТ, достигли 5-летней выживаемости, в то время как пациенты из груп-пы стандартной химиотерапии не пережили 2 года [47]. Еще одно исследование включало 250 пациентов с мета-статическими солидными опухолями -РМЖ, КРР, ОГШ, РЖ -которые получали стандартную химиотерапию с или без МЛТ 20 мг внутрь ежедневно.…”
Section: фундаментальная онкология и экспериментальная медицина • Fununclassified
“…In 2003, Paolo Lissoni, MD, chief of oncology at a large public hospital in northern Italy, and colleagues, showed that melatonin can "modulate the effects of cancer chemotherapy, by enhancing its therapeutic efficacy and reducing its toxicity." 54 It was only the latest in a long line of positive clinical trials on this topic.…”
Section: Melatoninmentioning
confidence: 99%
“…54 In 2003, Lissoni and colleagues looked at 5-year survival rates from metastatic NSCLC. One hundred patients received the standard drugs cisplatin and etoposide, with or without the concomitant administration of melatonin (20 mg/d orally in the evening).…”
Section: Melatoninmentioning
confidence: 99%